Efficiency of adaptive filter with envelope tracking algorithm when receiving signals with multi-position PSK against the background of non-fluctuation interferences - G. V. Kulikov; Trung Tien Do (Российский технологический журнал)
The energy and spectral advantages of signals with phase-shift keying predetermined their widespread use in modern digital navigation, communications and television systems. The use of this type of signal in a multi-position format with an increased number of possible phase states allows increasing the information capacity of the channel signal, and consequently the throughput rate of radio channels. The presence of non-fluctuation interference in such radio channels greatly reduces the noise immunity of information reception. A well-known way to deal with such interference is to use adaptive non-recursive filters in the receiver. The article evaluates the effectiveness of using such a filter with an algorithm for setting weight coefficients that controls the constant envelope of a useful signal when receiving signals with multi-position phase shift keying against the background of noise and non-fluctuation interference. Two types of such interference are considered – harmonic and relayed. Using computer simulation, the optimal filter parameters (adaptation coefficient and its length) are determined; the effect of the filter on the noise immunity of the quadrature signal receiver with multi-position phase shift keying for various combinations of interference and their intensity is estimated. It is shown that such an adaptive filter can successfully cope with the most dangerous sighting harmonic interference.